The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/genes9040218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Natural Populations of the Endangered Conifer Thuja koraiensis Using Microsatellite Markers by Restriction-Associated DNA Sequencing

Abstract: Thuja koraiensis Nakai is an endangered conifer of high economic and ecological value in Jilin Province, China. However, studies on its population structure and conservation genetics have been limited by the lack of genomic data. Here, 37,761 microsatellites (simple sequence repeat, SSR) were detected based on 875,792 de novo-assembled contigs using a restriction-associated DNA (RAD) approach. Among these SSRs, 300 were randomly selected to test for polymorphisms and 96 obtained loci were able to amplify a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
(92 reference statements)
2
6
0
Order By: Relevance
“…The structure of Moroccan populations, calculated by AMOVA, had revealed a high level of variation within populations (85%) and a low level of variation among populations (11%). Our results are in line with the previous study on genetic diversity of T. articulata (Sánchez-Gómez et al, 2013) and other Cupressaceae species (Meloni et al, 2006;Liu et al, 2013;Hou et al, 2018) that maintain more variation within species and within populations species than species with other life forms but have less variation among populations (Vashishtha et al, 2013). The genetic differentiation values detected for gymnosperms (Gst = 0.18) (Nybom and Bartish, 2000) are similar to our Genetic structure of 129 genotypes assessed by STRUCTURE software (20 independent runs of each K value (from K = 1 to 10) were performed with 50,000 as the burn-in and 100,000 iterations.…”
Section: Populationsupporting
confidence: 93%
See 1 more Smart Citation
“…The structure of Moroccan populations, calculated by AMOVA, had revealed a high level of variation within populations (85%) and a low level of variation among populations (11%). Our results are in line with the previous study on genetic diversity of T. articulata (Sánchez-Gómez et al, 2013) and other Cupressaceae species (Meloni et al, 2006;Liu et al, 2013;Hou et al, 2018) that maintain more variation within species and within populations species than species with other life forms but have less variation among populations (Vashishtha et al, 2013). The genetic differentiation values detected for gymnosperms (Gst = 0.18) (Nybom and Bartish, 2000) are similar to our Genetic structure of 129 genotypes assessed by STRUCTURE software (20 independent runs of each K value (from K = 1 to 10) were performed with 50,000 as the burn-in and 100,000 iterations.…”
Section: Populationsupporting
confidence: 93%
“…In our study, the gene flow (Nm = 3.29; Nm is the number of migrants per generation) showed a sort of continuity between the different populations of T. articulata insured by seed dispersal and pollen. In this case and being a wind-pollinated conifer, pollen can spread over long distances under proper environmental conditions (Lanner, 1966), which may explain the high level of genetic diversity (Hou et al, 2018). Our results are similar to Calocedrus macrolepis (Wang et al, 2004), Thuja sutchuenensis (Liu et al, 2013) and T. koraiensis (Liu et al, 2017) and higher than G. pensilis (Li and Xia, 2005), J. phoenicea (Meloni et al, 2006) and T. occidentalis (Pandey and Rajora, 2012).…”
Section: Populationsupporting
confidence: 66%
“…In this study, however, we found the cpSSR genetic diversity of T. sutchuenensis was not lower ( He = 0.23–0.53) than other narrow-ranged species such as the Camellia huana ( He = 0.339–0.605 for cpSSR, Ho = 0.353–0.605 for cpSSR) ( Li et al, 2020 ), or widespread species, for example, Pinus kesiya ( He = 0.654 for cpSSR) ( Rai and Ginwal, 2018 ) and Ambrosia trifida ( He = 0.203–0.645 for cpSSR) ( Sharma et al, 2020 ). T. sutchuenensis have comparable genetic diversity with the other two congener species, T. koraiensis (SSR He = 0.548) and T. occidentalis (SSR He = 0.574–0.624) ( Xu et al, 2013 ; Hou et al, 2018 ). This relatively high cpSSR genetic diversity of T. sutchuenensis might be due to current individuals from large populations that existed before in northern China, which indicates the likely effects of evolutionary history (from Northern China to the Daba Mountains) on genetic diversity.…”
Section: Discussionmentioning
confidence: 94%
“…For plants, molecular marker technology has become a popular method for studying the population genetics of species [17][18][19][20]. Selecting suitable molecular markers is the key to accurately assessing the genetic diversity and genetic structure of endangered species populations [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nSSRs stand out among the many known molecular markers [25]. Microsatellite markers have been successfully applied in various studies on conifer species, such as core collection sorting, genetic resource assessment and relationship establishment [17].…”
Section: Introductionmentioning
confidence: 99%